ANALYSIS OF THE ROLE OF SUSTAINABILITY ACCOUNTING IN IMPROVING THE ENVIRONMENTAL AND SOCIAL PERFORMANCE OF MANUFACTURING COMPANIES IN INDONESIA. - Wilda Sri Munawaroh Harahap (CV. Barokah Publsiher, 2025)
This study aims to analyze the role of sustainability accounting in improving the environmental and social performance of manufacturing companies in Indonesia. With the growing global awareness of sustainability issues, companies are expected not only to pursue financial profit but also to consider the impact of business activities on the environment and society. Through a qualitative approach involving literature reviews and case studies, this research finds that proper implementation of sustainability accounting can positively impact transparency, accountability, and corporate decision-making in managing environmental and social issues. The results also indicate that companies that consistently apply sustainability accounting show improvements in reputation, operational efficiency, and regulatory compliance